2007
DOI: 10.1002/ccd.21240
|View full text |Cite
|
Sign up to set email alerts
|

Standardized evaluation and reporting of stent fractures in clinical trials of noncoronary devices

Abstract: As the proliferation of minimally invasive revascularization strategies continues, the stability of metallic endoprostheses is increasingly critical. Uniform surveillance of these devices for fracture and disarticulation is important in order to compare the relative merits of various stent-based devices in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 25 publications
0
70
0
1
Order By: Relevance
“…In patients in whom stent fracture was suspected by duplex sonography, further evaluation for stent fractures was performed by biplanar fluoroscopy according to the classification used by Jaff et al 18 Visualization of stent grafts was performed using the stent-boost technique.…”
Section: Follow-upmentioning
confidence: 99%
“…In patients in whom stent fracture was suspected by duplex sonography, further evaluation for stent fractures was performed by biplanar fluoroscopy according to the classification used by Jaff et al 18 Visualization of stent grafts was performed using the stent-boost technique.…”
Section: Follow-upmentioning
confidence: 99%
“…A review of the literature found no mention of stent fractures as a periprocedural complication involving the use of balloon-expandable stents in the iliac arteries. Allie et al have suggested a 4-type classification system for nitinol stent fracture in peripheral vessels, which was later expanded to 5 types by Jaff et al (10). A type I fracture involves only a single strut; type II involves multiple struts that can occur at different sites; type III involves multiple strut fractures resulting in complete transverse fracture without displacement; type IV result in a complete transverse linear fracture with stent displacement; and type V is spiral fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Stent fractures (SFs) may be associated with unanticipated late complications, including clinical in-stent restenosis (ISR), stent thrombosis and aneurysm formation [31][32][33][34][35]. "Type IV" stent fractures have been defined by Jaff et al [36] as a complete transverse, linear fracture of stent struts along with displacement of the stent fragments. Popma et al [31] presented excellent angiographic evidence of fracture Types II-IV and noted a high incidence percentage of angiographic restenosis associated with the Type IV fracture (seven out of 18 patients).…”
Section: Introductionmentioning
confidence: 99%